Stigma Orang dengan Gangguan Jiwa di Program Desa Siaga Sehat Jiwa - Zaini, Mad; Komarudin, Komarudin; Abdurrahman, Ginanjar (Jurnal Kesehatan Holistic, 2024)
the care of people with mental illness, especially those who are treated at home. Botolinggo Village is one of the villages that has a mental health alert village program. This study aims to determine the description of the stigma of people with mental disorders in Botolinggo Village, Bondowoso Regency. This research design uses a quantitative descriptive approach. The population in this study were 52 respondents who were taken using purposive sampling. The instrument used in this study was community attitudes toward the mentally illness (CAMI). Univariate data analysis uses mean, median and standard deviation, while bivariate data uses Pearson correlation test. The results of univariate analysis show that the stigma of mental disorders in Botolinggo Village, Bondowoso Regency tends to be low and has a positive attitude towards mental health problems that exist in the community. Based on the stigma domain, the highest domain is the benevolence domain, which means that the local community has a good, sympathetic and humanist attitude towards people with mental disorders. This is assumed to be related to the age of the respondents. In addition, the existence of the Desa Siaga Sehat Jiwa (DSSJ) Program in collaboration between the Botolinggo Village Government and Muhammadiyah Jember University through the program Matching Fund 2023 made a positive contribution to community assessments and attitudes towards people with mental illness in Botolinggo Village.